Relationship between the heterogeneity of low-permeability reservoirs and the dynamic evolution of fractures under uniaxial compression conditions by CT scanning: A case study in the jiyang depression of Bohai Bay Basin, China - Li, Li; Shi, Guangyao; Zhang, Yixin; Liu, Xiangwei (Frontiers in Earth Science, 2023)
Based on an analysis of core fractures and computed tomography scanning by X-ray under uniaxial compression tests with loading and unloading, this study investigated the three-dimensional evolution of fracture initiation and propagation in different heterogeneity conditions of low-permeability reservoirs. Reservoir heterogeneity affected the 3D dynamic development of fractures. With increasing loading value, fractures with strong heterogeneity in low-permeability reservoirs followed the development sequence from shallow to deep depth in the profile. When the fracture tip reached the incompetent layer, propagation stopped. Subsequently, when the deformation continued to increase, the fracture crossed the incompetent layer and initiated a new fracture at the front end. Therefore, the across-bedding and through-going macro fractures formed in conjugate sets or were Y-shaped, with roughly equal spacing. In the plane, the fractures initiated along the pre-existing bedding parallel fracture and further propagated into large fractures. Consequently, they formed a net-shaped fracture from the edge to the center, with a long development period. These fractures intersected to form a complex, interconnected, and high-fracture-density system in three dimensions. Under the same loading value, owing to uniform lithology, the formation of micro-fractures in the weak heterogeneity of low-permeability reservoirs is difficult. Furthermore, long shear fractures were only produced in a relatively short formation period with a low fracture density. In the plane, the fractures stepped in an en-énchelon and terminated with horse-tailing microfractures. Moreover, the strong heterogeneity of low-permeability reservoirs was more favorable for producing fractures. The fracture volume was 13.17% of the total sample volume compared to 0.67% in the weak-heterogeneity reservoir under the same loading compression. Furthermore, a better fracturing effect was achieved by fracturing along the direction >50° with the natural fracture and under the condition of small differential horizontal stresses.